PRODUKTIVITAS DAN EFISIENSI PEMANENAN KAYU DENGAN TEKNIK PENEBANGAN POHON SERENDAH MUNGKIN DI HUTAN PRODUKSI ALAM: STUDI KASUS DI TIGA PERUSAHAAN HUTAN DI KALIMANTAN TENGAH - Maman Mansyur Idris; Sona Suhartana (Jurnal Penelitian Hasil Hutan, 1995)
This  paper   presents   the  results   of  the  study  of  wood  harvesting   productivity  and  efficiency when   practicing   the   lowest  possible   felling   technique.  The  case   study   was  selected   in   three logging   companies    in  Central    Kalimantan    in   1994.   Then,    the   results   are  compared   lo  those obtained  from  conventional   felling  technique.the  results  of the  study  are  as  follow  :1.The   results   of  wood   harvesting    productivity   is  25,2 m3/hr   for   lowest   possible   felling technique  and  28,8  m3/hr for   conventional  felling.  This difference   is  statisticallv   significant.2.The  average   of  wood  harvesting    efficiency    is  86, 1   % for   lowest   possible   felling    technique and   82,1   % for  conventional    felling   technique.   This   difference of  1,28 m3/tree  is  highl significant.3.The  average   of stwnp  height   when  practicing    the  lowest possible  felling technique  is 0,45 m, while for  conventional  felling  technique   is 1,21 m.